A novel hybrid enhanced oil recovery method by smart water-injection and foam-flooding in carbonate reservoirs - Hassan, A.M. (Society of Petroleum Engineers, 2019)
This contribution focuses on recovery of oil by using a newly hybrid Enhanced Oil Recovery (EOR) method, which combines smart water (i.e. ionically modified brine) and foam flooding of light oil with dissolved carbon dioxide at high pressure in carbonate reservoirs. Ionically modified brine (i.e. low salinity) has a dual improvement effect. It not only leads to more stable foam lamellae, but also helps to change the carbonate rock wettability from oil-wet to more water-wet, which has for some conditions more favorable relative permeability behavior. The mechanism for the modified permeability behavior in the presence of ionically modified brine is only partly understood. Therefore, we use the DLVO (i.e. Derjaguin, Landau, Verwey, and Overbeek) theory (i.e. which considers double layer repulsion, born repulsion, and Van der Waals attraction) and surface complexation modeling to better understand the mechanism(s) of ionically modified brine as wettability modifier and foam stabilizer. We use the PHREEQC software to obtain the equilibrium concentrations and surface potential and to study the effect of salinity and carbon dioxide gas pressure for a given choice of the surfactant (i.e. carboxylic acid R-COOH). It is conjectured that high carbon dioxide pressures have a destabilizing effect on the film, as they reduce the surface potential. A reduced surface potential leads to a decreasing electrostatic double layer repulsion and thus destabilizes the stability of the foam film, whereas low salinity leads to less screening of the surface potential and thus improves the stability of the foam film. The low-salinity flow is characterized by a high residual oil saturation and low end-point permeability for the two-phase oil-water flow. For the calcite surface an enhanced stability help to stabilize the water film on the calcite surface if the oil-water surface charge has the same sign as the surface charge on the calcite surface. Our calculations show the pH range where the sign of these charges is the same or opposite at low-salinity and high-salinity conditions. Admittedly, these calculations only show trends, but can be used to delineate optimal conditions for the use of combined Smart Water Assisted Foam (SWAF) flooding. Copyright 2019, Society of Petroleum Engineers.